PENGUKURAN KINERJA UKM PENGHASIL BUSANA MUSLIM TASIKMALAYA DENGAN METODE BALANCE SCORECARD UNTUK MENCIPTAKAN SUSTAINABLE COMPETITIVE ADVANTAGE DALAM UPAYA MENINGKATKAN PROFITABILITAS - Purwanto (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2016)
ABSTRACT : The business environment is increasingly competitive and complex challenges faced by the company. For that companies need to create a performance measurement system that is better than the system used by the traditional view. Thus emerged a new thinking pioneered by Kaplan and Norton introduced the Balanced Scorecard method. The Balanced Scorecard has a privilege in terms of coverage measurement is more comprehensive because it includes four items, there are financial perspectives, customer, internal business process, and learning and growth. Through the balanced scorecard enables managers to improve the effectiveness and company performance continuously / sustainable competitive advantage and maintain customer satisfaction. The last but not least to get profitabllity.